Penjernihan Air Sumur Secara Kimia dan Fisika untuk Menurunkan Kadar CaCO3 dan Conductivity - Debora, Ratu Mayoreta (Journal of Industrial Process and Chemical Engineering (JOICHE), 2023)
The well water purification process is carried out so that well water can be used as cooling water in industrial equipment and does not pollute the environment around the industry. The purification of well water uses two methods, namely chemically and physically. Well water purification materials in the chemical process use nalcolyte 8100, sodium hypoclorite 12%, and nalcolyte 7408. The physics tools used to purify well water are sand filters, carbon filters, cartridges, and RO membranes. The parameters and results in this well water purification process include pH analysis of 6, conducticity of 91.7 μS / cm, colorless or clear, odorless, and CaCO3 levels of 0 mg / L.Keyword: Flokulasi, koagulasi, membran, reverse osmosis.